Dementia During the COVID-19 Pandemic: Experiences From Clinicians, Patients, and Caregivers in Switzerland - Neumann, Eileen; Ballmer, Lisa; Studhalter, Olivia; Schmid, Nicole; Jung, Hans H. (Gerontology and Geriatric Medicine, 2023)
Background: The COVID-19 pandemic had a significant impact on the Swiss health care system, affecting especially vulnerable people, such as patients suffering from dementia. The purpose of this study was to investigate the challenges experienced by dementia patients, their carers, and clinicians during the pandemic in Switzerland. Methods: An online survey was sent to all memory clinics in the German speaking part of Switzerland. Patients diagnosed with dementia and their carers were recruited for semi-structured telephone interviews at the memory clinic of the University Hospital Zurich. Results: A total of 28 clinicians, 17 carers, and seven patients participated in this study. According to the clinicians, all aspects of clinical work were affected by the pandemic. Carers did not perceive a significant role of the pandemic in the disease progression of the patients, despite many challenges faced. Patients described a high level of conscientiousness during the pandemic. Recommendations for future scenarios were provided from all groups. Conclusion: In order to increase the systemic resilience of the Swiss health care system, it is important to consider the experiences and recommendations of vulnerable groups and health care professionals for future public health measures and policies.